THE INFLUENCE OF LEADERSHIP STYLE AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE SATISFACTION - Alvandy Agung Pramudji Mintia; Seno Sudarmono Hadi (Sean Institute, 2023)
To determine the significant influence of leadership style and work motivation simultaneously on employee performance satisfaction. This research shows that leadership style significantly affects work motivation and performance satisfaction. The research data consists of two independent variables, namely leadership style and work motivation, as well as the dependent variable, namely performance satisfaction. The analysis results show that all items in the leadership style, work motivation, and performance satisfaction scales are valid and reliable. The linearity test shows a significant linear relationship between performance satisfaction, leadership style, and work motivation. The t-test shows that leadership style does not significantly influence performance satisfaction, while work motivation positively and significantly influences performance satisfaction. The F test shows a significant simultaneous influence between leadership style, work motivation, and performance satisfaction. Based on the multiple linear regression test, a regression equation shows the relationship between these variables. The variables Leadership Style and Work Motivation influence Performance Satisfaction by 52.3%, while the rest is influenced by other factors that were not studied. This research provides insight into the factors contributing to leadership style, work motivation, and performance satisfaction.